2008
DOI: 10.1128/iai.01643-07
|View full text |Cite
|
Sign up to set email alerts
|

LipL32 Is an Extracellular Matrix-Interacting Protein of Leptospira spp. and Pseudoalteromonas tunicata

Abstract: LipL32 is the major outer membrane protein in pathogenic Leptospira. It is highly conserved throughout pathogenic species and is expressed in vivo during human infection. While these data suggest a role in pathogenesis, a function for LipL32 has not been defined. Outer membrane proteins of gram-negative bacteria are the first line of molecular interaction with the host, and many have been shown to bind host extracellular matrix (ECM). A search for leptospiral ECM-interacting proteins identified the major outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
0
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 30 publications
11
144
0
17
Order By: Relevance
“…LipL32 is expressed at high levels on the bacterial surface during both cultivation and natural infection (24). The protein is immunogenic and some studies have implicated LipL32 as an extracellular matrix-binding protein, interacting with collagen type IV, plasma fibronectin, and laminin (11,12). Recently, Vieira et al (13) showed that LipL32 is able to bind to human plasminogen, the inactive precursor of the extracellular proteinase plasmin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LipL32 is expressed at high levels on the bacterial surface during both cultivation and natural infection (24). The protein is immunogenic and some studies have implicated LipL32 as an extracellular matrix-binding protein, interacting with collagen type IV, plasma fibronectin, and laminin (11,12). Recently, Vieira et al (13) showed that LipL32 is able to bind to human plasminogen, the inactive precursor of the extracellular proteinase plasmin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with recombinant LipL32 revealed that this highly immunogenic protein can induce a robust inflammatory response in renal proximal tubule cells (9,10). Furthermore, LipL32 may contribute to host colonization, because it has been demonstrated that it interacts with extracellular matrix (ECM) 3 components, such as collagen type IV, plasma fibronectin, and laminin (11,12) and binds human plasminogen (13).…”
mentioning
confidence: 99%
“…This allows for an optimal recovery of these proteins at the purification stage. The following is a sample of papers that used this protocol to recover biotinylated proteins: [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Following the pre-adsorption phase, the column was then washed with 16 ml of 10 % acetic acid and 0.1 M NaHPO 4 until the pH of the flow-through was >6.8.…”
Section: Biotin Avidin Columnmentioning
confidence: 99%
“…Apesar disso, a ligação de LipL32 com laminina e colágeno foi demonstrado (HAUK et al, 2008;HOKE et al, 2008). Outra proteína interessante presente na membrana das leptospiras consiste na família de proteínas que apresentam domínios do tipo imunoglobulinas (Ig), nomeadas como LigA, LigB e LigC.…”
Section: Mecanismos De Patogenicidadeunclassified
“…Várias proteínas de leptospiras com propriedades de ligação específica a laminina e a outros componentes da ECM foram identificadas pelo nosso grupo (ATZINGEN et al, 2008;ATZINGEN et al, 2009;BARBOSA et al, 2006;DOMINGOS et al, 2015;DOMINGOS et al, 2012;FERNANDES et al, 2014;FERNANDES et al, 2012;LONGHI et al, 2009;MENDES et al, 2011;OLIVEIRA et al, 2011;OLIVEIRA et al, 2010; __________________________________________________________Resultados e Discussão 113 2013; SOUZA et al, 2012;VIEIRA et al, 2010b). Outros grupos também identificaram proteínas com capacidade de adesão (CARVALHO et al, 2009;CHOY et al, 2007;HAUK et al, 2008;HOKE et al, 2008;LIN et al, 2009;STEVENSON et al, 2007). De maneira geral, esses dados demonstram o potencial que as leptospiras patogênicas apresentam em aderir nas células do hospedeiro a fim de estabelecer uma infecção.…”
Section: Adesão Das Proteínas Recombinantes a Componentes Da Matriz Eunclassified